Turbinate surgery: which rhinitis are most at risk - Gelardi, Matteo; Giancaspro, Rossana; Bocciolini , Corso; Salerni, Lorenzo; Cassano, Michele (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Allergic rhinitis (AR) and non-allergic rhinitis (NAR) belong to field of vasomotor rhinitis, characterized by nasal hyper-reactivity. Since AR and NAR are two separate nosological entities, these rhinopaties can coexist in the same patient in up to 15-20% of cases. Overlapped rhinitis (ORs) are associated with intense and persistent symptoms and are often misdiagnosed. Typically, when medical treatment fails, patients undergo turbinate surgery. We evaluated which rhinopaties are most at risk of undergoing turbinate surgery and established the percentage of ORs. Methods: The study included 120 patients undergoing turbinate surgery for turbinate hypertrophy. Anterior rhinoscopy, nasal endoscopy, nasal cytology, skin prick tests (SPT) and/or specific IgE serum assays (CAP-RAST) were performed preoperative on all patients.Results: Among patients with indication for turbinate surgery, 75% suffered from AR, whereas 25% of them had NAR. On closer analysis, only 7 (8%) of allergic patients presented a “pure” allergy.  NAR with eosinophils and mast cells (NARESMA) represented the most common type of superimposed rhinitis (62.5%), while NAR with mast cells (NARMA) and with eosinophils (NARES) represented 25% and 12.5% of the superimposed forms, respectively.Conclusion: Most of the patients undergoing turbinate surgery actually have complex forms of rhinitis. The non-allergic component of ORs often causes therapeutic failure. NARESMAs overlapping ARs are at most risk of undergoing turbinate surgery. Correctly framing a rhino-allergological patient is essential in order to guarantee the most adequate treatment. Hence the importance of introducing in clinical practice investigations, including allergy tests and nasal cytology.